Revealing ultra-high-energy cosmic ray acceleration with multi-messenger observations of the nearby GRB 980425/SN 1998bw - Mirabal, Nestor (IOP Publishing, 2023)
The origin of ultra-high energy cosmic rays (UHECRs) is one of the most mystifying issues in astroparticle physics. It has been suggested that gamma-ray bursts (GRBs) are excellent acceleration sites for cosmic rays. The propagation of UHECRs from the GRB host galaxy to the Earth should generate delayed secondary photons and neutrinos. Here we present a dedicated search for delayed UHECR and neutrino emission centered around the position of nearby GRB 980425/SN 1998bw. Located at a distance of 36.9 Mpc, GRB 980425/SN 1998bw is well within the Greisen-Zatsepin-Kuzmin (GZK) distance horizon. We find no evidence for UHECR or neutrino clustering around the GRB 980425/SN 1998bw position between 2004 and 2020. Under ideal propagation conditions, we propose that it might be possible to detect an excess from delayed UHECRs around GRB 980425/SN 1998bw within the next 100 years if the intergalactic magnetic field (IGMF) strength is B ≤ 3×10⁻¹³ G.